Comparative effectiveness and safety of edoxaban versus warfarin in patients with atrial fibrillation: A nationwide cohort study. Issue 5 (June 2022) - Nielsen, Peter B; Søgaard, Mette; Jensen, Martin; Ording, Anne G; Lip, Gregory YH
Background and purpose: The effectiveness and safety of edoxaban 60 mg and 30 mg for stroke prevention compared with warfarin in patients with atrial fibrillation have not been well-described in a nationwide cohort of Caucasian patients treated in standard clinical practice. Methods: We used Danish nationwide registries to identify patients with atrial fibrillation during June 2016 and November 2018 who were treated with edoxaban or warfarin and computed rates per 100 person-years of thromboembolic, all-cause mortality, and bleeding events using an inverse probability of treatment weighting approach to account for baseline confounding. We used weighted pooled logistic regression to compute hazard ratios with 95% confidence intervals comparing events between edoxaban 60 mg and warfarin users; edoxaban 30 mg was not included in formal comparisons. Results: We identified 6451 atrial fibrillation patients, mean age was 72 years and 40% were females. A total of 1772 patients were treated with edoxaban 60 mg, 537 with edoxaban 30 mg, and 4142 with warfarin. The median CHA2 DS2 -VASc score was similar between warfarin and edoxaban 60 mg with a score of 3 (interquartile range (IQR) 2–4). In the inverse probability of treatment-weighted pseudo-population, the thromboembolic event rate for edoxaban 60 mg was 0.95 and 1.0 for warfarin, corresponding weighted hazard ratio of 1.00 (95% confidence intervals (CI) 0.59, 1.71). Edoxaban 60 mg users were associated with lower rates of all-cause mortality (3.93) compared to warfarin (6.04), with a hazard ratio of 0.64 (95% CI 0.47 to 0.88). The event rates for bleeding were 3.36 and 3.14, respectively; hazard ratio 1.09 (95% CI 0.77, 1.57). Conclusion: Edoxaban 60 mg is a safe and effective treatment compared with warfarin for stroke prevention in routine clinical care for Danish (mainly Caucasian) patients with AF, with non-significantly different risks for stroke and clinically relevant bleeding, but lower all-cause mortality.